2016
DOI: 10.1097/eja.0000000000000516
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of local infiltration analgesia in the early postoperative period after total knee arthroplasty

Abstract: LIA is effective for acute pain management after TKA. Intraoperative peri-articular but not intra-articular injection may be helpful in pain control up to 24 h. The use of postoperative intra-articular catheter placement is still inconclusive. The benefit of LIA as an adjunctive treatment to regional anaesthesia was not demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(54 citation statements)
references
References 69 publications
1
48
0
5
Order By: Relevance
“…Although numerous meta-analyses have attempted to determine whether FNB or ACB is superior, conflicting results have emerged 3135. While some meta-analyses have found ACBs to be equivalent to FNBs in terms of pain control at rest and with movement, strength of quadriceps and adductor muscles, LOS, and incidence of nausea and vomiting,31 others have found ACBs to be superior.…”
Section: Multimodal Analgesiamentioning
confidence: 99%
See 2 more Smart Citations
“…Although numerous meta-analyses have attempted to determine whether FNB or ACB is superior, conflicting results have emerged 3135. While some meta-analyses have found ACBs to be equivalent to FNBs in terms of pain control at rest and with movement, strength of quadriceps and adductor muscles, LOS, and incidence of nausea and vomiting,31 others have found ACBs to be superior.…”
Section: Multimodal Analgesiamentioning
confidence: 99%
“…Seangleulur et al35 examined the analgesic efficacy of PAI compared to placebo/no injection in patients undergoing TKA. The PAI group had lower pain scores, opioid consumption and postoperative nausea/vomiting, higher range of motion at 24 hours, and shorter LOS than no injection or placebo 35.…”
Section: Multimodal Analgesiamentioning
confidence: 99%
See 1 more Smart Citation
“…[7,8] A mixture that comprises a long-acting local anesthetic, a nonsteroid anti-inflammatory drug and epinephrine is most commonly used in local infiltration. LIA is a promising method with fewer side effects that offers early mobilization without weakness of the quadriceps muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Local infiltration anesthesia (LIA) has been identified a successful and easy way to management postoperative pain, and promote early mobilization after TKA [8]. A meta-analysis indicated that LIA shows better pain control than FNB, which is considered to be the gold standard anesthesia method [9].…”
Section: Introductionmentioning
confidence: 99%